2020
DOI: 10.1002/pds.5021
|View full text |Cite
|
Sign up to set email alerts
|

Medication persistence of targeted immunomodulators for plaque psoriasis: A retrospective analysis using a U.S. claims database

Abstract: Purpose Studies of medication persistence in plaque psoriasis have shown inconsistent results, likely due to differing definitions of nonpersistence and of the permissible gap between refills. Also, medication persistence information for two recently approved drugs, apremilast and ixekizumab, is limited. Methods We use the Truven Health MarketScan claims database to assess persistence for six drugs: adalimumab, apremilast, etanercept, ixekizumab, secukinumab, and ustekinumab. We define the permissible gap in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Our 12‐month drug‐survival rates among biologic‐experienced patients of 65% for ixekizumab vs 34% for TNFi, and 54% for non‐ixekizumab IL‐17i initiators, are comparable to those recently reported for adalimumab (12 months survival: 55% for ixekizumab vs 47% for adalimumab) 3 and secukinumab (12 months survival: 57% for ixekizumab vs 50% for secukinumab) 25 . The higher drug survival observed among ixekizumab users is consistent despite most users being biologic‐experienced, a subgroup of patients who have been shown to have lower drug survival than biologic‐naïve users 38, 39 . Notably, drug survival for all three groups was similar for approximately 6 months, at which point the survival curves separated and ixekizumab performed better out to 24 months of follow‐up.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our 12‐month drug‐survival rates among biologic‐experienced patients of 65% for ixekizumab vs 34% for TNFi, and 54% for non‐ixekizumab IL‐17i initiators, are comparable to those recently reported for adalimumab (12 months survival: 55% for ixekizumab vs 47% for adalimumab) 3 and secukinumab (12 months survival: 57% for ixekizumab vs 50% for secukinumab) 25 . The higher drug survival observed among ixekizumab users is consistent despite most users being biologic‐experienced, a subgroup of patients who have been shown to have lower drug survival than biologic‐naïve users 38, 39 . Notably, drug survival for all three groups was similar for approximately 6 months, at which point the survival curves separated and ixekizumab performed better out to 24 months of follow‐up.…”
Section: Discussionsupporting
confidence: 84%
“…25 The higher drug survival observed among ixekizumab users is consistent despite most users being biologic-experienced, a subgroup of patients who have been shown to have lower drug survival than biologic-naïve users. 38,39 Notably, drug survival for all three groups was similar for approximately 6 months, at which point the survival curves separated and ixekizumab performed better out to 24 months of follow-up.…”
Section: Resultsmentioning
confidence: 94%
“…Overall, patients with psoriasis in clinical practice settings who were treated with ixekizumab had significantly greater persistence with therapy vs. guselkumab when assessed using 45-day and 60-day allowable gaps, but no difference in persistence was observed between groups in the analysis when using a more generous 90-day allowable gap. Previous studies on persistence in psoriasis have used a range of allowable gaps from 45 to 150 days [16,23,24], and we have previously reported results for comparisons of ixekizumab and adalimumab or secukinumab based on a 60-day gap [17,18]. However, a recent analysis of multiple drugs for psoriasis found that persistence estimates for ustekinumab, which has a 12-week dosing interval, varied more widely depending on the allowable treatment gap than other drugs with shorter dosing and refill intervals [16].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies on persistence in psoriasis have used a range of allowable gaps from 45 to 150 days [16,23,24], and we have previously reported results for comparisons of ixekizumab and adalimumab or secukinumab based on a 60-day gap [17,18]. However, a recent analysis of multiple drugs for psoriasis found that persistence estimates for ustekinumab, which has a 12-week dosing interval, varied more widely depending on the allowable treatment gap than other drugs with shorter dosing and refill intervals [16]. Our results are consistent with this finding in that the significance of differences in persistence between ixekizumab, with typical maintenance dosing every 4 weeks, and guselkumab, with typical maintenance dosing every 8 weeks, varied depending upon the length of the allowable gap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation